Mengkaji Naskah Drama “Sepasang Merpati Tua” Karya Bakdi Soemanto Menggunakan Pendekatan Struktural Serta Nilai Pendidikannya - Anggita, Via; Waridah, Ira; Mutiara, Lia; Putra, Adita Widara (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Literary works are one of the communication media to narrow ideas or ideas to connoisseurs, one example is drama. In this case, the author examines the play entitled "A Pair of Old Doves" by Bakdi Soemanto using a structural approach to find out the structure used in the play. This research uses qualitative methods with descriptive so that it focuses on explanation through a description. Life is the theme of this drama script obtained by researchers. This drama uses a non-chronological plot, there are only 2 characters who have characterizations of the protagonist and antagonist, set in the house of the Kakek and Nenek before night, and the dialogue used is quite communicative.